Evaluation of the efficacy of MST-312, as a telomerase inhibitor, in the treatment of patients with multiple myeloma after stem cell transplantation - Zhou, Chengxiang; Liu, Shaoling (Cellular and Molecular Biology, 2022)
High-dose chemotherapy and stem cell transplantation are the best treatment options in patients with multiple myeloma. Numerous medicines have been studied as a maintenance treatment after transplantation. Still, the use of medications that, in addition to their maintenance properties, eliminate or delay relapse of the disease has always been researchers’ purpose. Therefore, this study was performed to evaluate the efficacy of MST-312 after stem cell transplantation in patients with multiple myeloma. For this purpose, 73 patients with multiple myeloma after stem cell transplantation were studied. Thirty-five patients were in the case group, and 37 patients were in the control group. The case group was treated with 100 mg/day MST-312. Stem cell survival was evaluated in the two groups. Also, the expression of TNFα and IL-6 genes were evaluated by the Real-time PCR technique. The results showed no significant difference between the two groups in terms of stem cell survival in the first year (P=0.72) and second years of treatment (P=0.66). But there was a significant difference between the two groups regarding progression-free survival (PFS) in the first year (P=0.041) and the second year (P=0.029). These results indicate that MST-312 inhibits the progress of the disease by inhibiting the telomerase activity of myeloma cells. Genetic evaluations also showed that IL-6 and TNF-α genes were significantly reduced in the case group. Therefore, it could be suggested that MST-312 has a selective inhibitory effect on myeloma cell growth and can be indicated as a suitable candidate for treating multiple myeloma.